2008
DOI: 10.1007/s10695-008-9234-1
|View full text |Cite
|
Sign up to set email alerts
|

Energy density of sub-Antarctic fishes from the Beagle Channel

Abstract: The energy density (ED) of nine species of sub-Antarctic fishes was estimated by calorimetry. The fish, seven notothenioids, one atherinopsid and one galaxiid, represents some of the more abundant species in the ichthyofauna of the Beagle Channel. Principal-components analysis (PCA) of the ED of the different organs/tissues indicated that PC(1) and PC(2) accounted for 87% of the variability. Separation along PC(1) corresponded to differences in muscle and liver energy densities whereas separation along PC(2) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Frequency of occurrence (FO) and relative proportion of each prey item in the diet were calculated using methods from [40] and compared to previously determined diet composition for Antarctic fur seals [32]. Upon identifying the main prey items, the size and energy content of the fish and squids found in the scats were taken from published sources [37, 39, 4143]. The size and energy content of squids were averaged per year and then over the 3 years from [32] to obtain squid estimates, as most of the squid beaks we found were unidentifiable.…”
Section: Methodsmentioning
confidence: 99%
“…Frequency of occurrence (FO) and relative proportion of each prey item in the diet were calculated using methods from [40] and compared to previously determined diet composition for Antarctic fur seals [32]. Upon identifying the main prey items, the size and energy content of the fish and squids found in the scats were taken from published sources [37, 39, 4143]. The size and energy content of squids were averaged per year and then over the 3 years from [32] to obtain squid estimates, as most of the squid beaks we found were unidentifiable.…”
Section: Methodsmentioning
confidence: 99%
“…Burkholder et al (1967) found that M. gregaria from Tierra del Fuego had a higher fat content and caloric value than Antarctic krill. M. gregaria and S. fuegensis had similar energy density (7.15 vs. 7.5 kJ g −1 , respectively; Romero et al 2006, Ciancio et al 2007, Scioscia et al 2014, much higher than all the fishes reported to date in BC (4.21− 6.26 kJ g −1 , Fernández et al 2009). These estimations were made on benthic Munida.…”
Section: Ww Speciesmentioning
confidence: 49%
“…Nevertheless, such variability could be attributed to the vitellogenesis which is an intrinsic process during sexual maturation (Sieiro et al, 2014). This increment in the ovary energy density from immature to mature individuals associated to yolk accumulation was previously found for this species by Rosa et al (2004b) as well as for other cephalopods (Lin et al, 2017), so as for other taxa such as fishes (Fernández et al, 2009). Therefore, the increase in the total energy in visceral tissues throughout sexual maturation could be due to, not only the organ's growth as revealed by the increase in condition and gonadosomatic indices observed in previous works as well (Otero et al, 2007;Sieiro et al, 2014), but also to the accumulation of lipids mostly triglycerides in the digestive gland and phospholipids in the ovary.…”
Section: Sexual Maturationmentioning
confidence: 52%